2020
DOI: 10.1038/s41374-019-0337-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of bone microstructure by propagation-based phase-contrast computed tomography using monochromatic synchrotron light

Abstract: Hard X-ray phase-contrast imaging is sensitive to density variation in objects and shows a dose advantage for in vivo observation over absorption-contrast imaging. We examined the capability of propagation-based phase-contrast tomography (PB-PCT) with single-distance phase retrieval for tracking of bone structure and mineral changes using monochromatic synchrotron light. Female mice underwent ovariectomy and drill-hole surgery in the right tibial diaphysis and were divided into two groups: OVX and OVX-E (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Additionally, to obtain optimal results in terms of both 3D reconstructed images and data sets to be used for quantitative measurements, phase contrast performed using conventional CT scanners [44][45][46] or synchrotron radiation sources [47][48][49][50][51] have been largely exploited. While the working principle of CT scanning is based on different X-ray absorbencies within the tested specimen, phase contrast scanning relies on the shift of the X-ray after passing through the scanned object [52].…”
Section: Operating Principle Of Laboratory Ct Equipmentmentioning
confidence: 99%
“…Additionally, to obtain optimal results in terms of both 3D reconstructed images and data sets to be used for quantitative measurements, phase contrast performed using conventional CT scanners [44][45][46] or synchrotron radiation sources [47][48][49][50][51] have been largely exploited. While the working principle of CT scanning is based on different X-ray absorbencies within the tested specimen, phase contrast scanning relies on the shift of the X-ray after passing through the scanned object [52].…”
Section: Operating Principle Of Laboratory Ct Equipmentmentioning
confidence: 99%
“…One unique imaging method is synchrotron radiation phase-contrast imaging computed tomography (SR-PCI). In a synchrotron, high-energy electromagnetic radiation is emitted by electrons moving at speeds close to that of light [ 32 , 33 ]. SR enables high-resolution imaging because it has high photon flux, stable sources, and an energy density 1000 times higher than conventional X-ray absorption imaging [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the research field, the application of SRμCT has shown superior 3D visualization capacity of cartilage, bone, and cartilage interface 15–19 . Aiming for better image quality, Matsumoto et al compared the imaging capacity between phase retrieval imaging versus conventional absorption imaging, and they confirmed that the phase contrast method did acquire considerably higher SNR and minimized edge‐enhancement effect 20 . Here in this study, SR‐based phase‐contrast μCT may provide us with a promising method to visualize the tissue components across BTI, at both native and injured status.…”
Section: Introductionmentioning
confidence: 99%